RINDERPEST IN CATTLE IN MOSUL AREA: CLINICAL OBSERVATIONS AND SEROLOGICAL DIAGNOSIS - A.Yousif, Y.; I. Sawa, M.; M. Zenad, M. (The Iraqi Journal of Veterinary Medicine, 1989)
Outbreaks of rinderpest in cattle occurred in Mosul area between February to June 1987. The morbidity and mortality rates were 45.9% and 19.3%, respectively. The disease was characterized by pyrexia, nasal discharge, lacrimation, hyperemic mucous membranes, anorexia, diarrhoea, lesions in the buccal cavity, respiratory distress and reduced rumen motility. Haematological studies revealed leukopenia and concurrent infection with theileriosis and anaplasmosis in 26.6% of RP affected cattle. Rinderpest viral antigens were detected in mesentric and visceral lymphnodes and spleen of the affected animals by agar gel diffusion test